A modified fracture assessment method for pipelines under combined inner pressure and large-scale axial plastic strain. (February 2017) - Jia, Pengyu; Jing, Hongyang; Xu, Lianyong; Han, Yongdian; Zhao, Lei
Highlights: The solution of Kastner was modified based on von Mises criterion. An empirical formula for γ was developed. The formula for γ is verified to be valid for cracked pipes under pressure and axial strain. Abstract: Owing to ground movement, in-service pipelines may be subjected to large scale axial plastic strain. Therefore, determining the fracture capacity of pipelines with crack-like defects is a key issue that needs to be addressed. In this study, to conduct an engineering critical assessment (ECA) for in-service pipelines, the limit load solution of Kastner for pipelines with circumferential surface cracks under tension was modified based on the von Mises yield criterion. Then, the limit load solution of Kastner was adapted to the situation under combined inner pressure and axial plastic strain. Furthermore, the optimised reference stress method was applied to improve the accuracy of the ECA for in-service pipelines. Finally, the formula for the non-dimensional parameter, γ, was developed.